2000
DOI: 10.1046/j.1523-1747.2000.00172.x
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of Dermatitis Herpetiformis and Celiac Disease in Monozygous Twins

Abstract: Celiac disease can be defined as the classical manifestation of gluten sensitivity, which primarily affects the small intestine. Gluten sensitivity has also a skin manifestation, i.e., dermatitis herpetiformis. Both diseases have a strong genetic association with HLA DQ on chromosome 6. In this study we tried to estimate how much different clinical expressions of gluten sensitivity are determined by genetic factors, and hence how feasible they are for genetic mapping; therefore, we studied all six monozygous t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 34 publications
1
51
0
3
Order By: Relevance
“…DH, whereas others with the same genetic background develop only gluten enteropathy without the rash and immunoglobulin (Ig)A1 deposits, i.e. CD [7].…”
Section: Introductionmentioning
confidence: 99%
“…DH, whereas others with the same genetic background develop only gluten enteropathy without the rash and immunoglobulin (Ig)A1 deposits, i.e. CD [7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the concordance rate of monozygotic twins is significantly higher than that of HLA-identical dizygotic twins (30%), (Romino et al, personal communication). 5,6 Assuming a multiplicative model of disease predisposing genes, the overall importance of non-HLA genes has been calculated to be greater than that of the HLA genes. 3,7 Despite this, knowledge about non-HLA genes that predispose to CD is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…E-mail : jukka.partanen!bts.redcross.fi genetic component is important too, as approximately 10-19 % of first-degree relatives are affected (Mearin et al 1983 ;Auricchio et al 1988 ;Hervonen et al 2002). Twin studies (Polanco et al 1981 ;Bardella et al 2000 ;Hervonen et al 2000) and studies of HLA identical sibs (Petronzelli et al 1997) have also indicated the importance of genetic factors. The only genetic locus indisputably associated with cCD and DH is the HLA DQ on chromosome 6.…”
Section: mentioning
confidence: 99%
“…As genetically identical twins can differ in outcome between cCD and DH (Walker-Smith, 1973 ;Jepsen & Ullman, 1980 ;Kosnai et al 1985 ;Hervonen et al 2000) this may be determined, at least in some cases, solely by environmental factors. …”
Section: mentioning
confidence: 99%